Effect of destination image, amenities on revisit intention with visitor satisfaction - Hadiwijaya, Hendra; Yustini, Tien; Annisa, Mutiara Lusiana (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This study aims to analyze the influence of Destination Image and Amenities on Revisit Intention with Visitor Satisfaction as an intervening variable at Balaputra Dewa Museum. The research seeks to understand how these factors contribute to improving the visitor experience and encouraging return visits. Research Methodology: The research employs a quantitative approach using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Data were collected through questionnaires distributed to 150 visitors of the Balaputra Dewa Museum, measured using a Likert scale. The model tested direct and indirect relationships between Destination Image, Amenities, Visitor Satisfaction, and Revisit Intention. Results: The findings indicate that Destination Image and Amenities significantly impact Revisit Intention. Visitor Satisfaction mediates the relationship between Destination Image and Revisit Intention, as well as between Amenities and Revisit Intention. Destination Image was shown to have a stronger influence on revisit intention compared to amenities. Indirect effects underscore the importance of visitor satisfaction in maximizing the impact of destination attributes. Conclusion: This study shows that Visitor Satisfaction helps explain how Destination Image and Amenities influence Revisit Intention at the Balaputra Dewa Museum, adding to knowledge in tourism and destination management. Limitations: The study is limited to one museum, which may reduce its applicability to other cultural or tourism sites. The cross-sectional data does not reflect long-term changes in visitor perceptions. Contributions: This research contributes to tourism management literature by emphasizing the role of destination image and amenities in fostering visitor satisfaction and revisit intention, providing insights for museum managers and policymakers. Novelty: The study introduces Visitor Satisfaction as an intervening variable, offering a deeper understanding of how satisfaction bridges the relationship between Destination Image and Amenities with Revisit Intention.